2018
DOI: 10.1371/journal.pone.0194103
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for pregnant women living in rural, agricultural villages to accessing antenatal care in Cambodia: A community-based cross-sectional study combined with a geographic information system

Abstract: BackgroundMaternal morbidity and mortality is still a major public health issue in low- and middle-income countries such as Cambodia. Improving access to antenatal care (ANC) services for pregnant women has been widely recognized as one of the most effective means of reducing maternal mortality and morbidity. As such, this study examined the barriers for pregnant women living in rural, agricultural villages to accessing ANC based on data collected in the Ratanakiri province, one of the least developed province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
(60 reference statements)
1
37
0
1
Order By: Relevance
“…desire to bury the placenta near their home. These factors may have negative influences on MHS use, compared with urban women who may be more educated and less influenced by traditional beliefs [22,23]. The low use of MHS outside urban areas may also be attributable to health system factors such as scarcity of health facilities, poor infrastructure, and lack (or absence) of healthcare providers in low volume facilities, especially in rural and island districts [24], as well as abusive and disrespectful maternity care [25].…”
Section: This Suggested That Area Of Residence May Play a Role In Ancmentioning
confidence: 99%
“…desire to bury the placenta near their home. These factors may have negative influences on MHS use, compared with urban women who may be more educated and less influenced by traditional beliefs [22,23]. The low use of MHS outside urban areas may also be attributable to health system factors such as scarcity of health facilities, poor infrastructure, and lack (or absence) of healthcare providers in low volume facilities, especially in rural and island districts [24], as well as abusive and disrespectful maternity care [25].…”
Section: This Suggested That Area Of Residence May Play a Role In Ancmentioning
confidence: 99%
“…In low-income countries, the rate is only 40%, and in rural areas and poorer communities, utilisation is much lower 2. Many studies in developing countries have identified an inverse relationship between distance to a health facility and the utilisation of health services 6–12. In a systematic review of 108 studies, 77% identified a distance decay association, where patients living further away from healthcare facilities had worse health outcomes than those who lived closer 13…”
Section: Introductionmentioning
confidence: 99%
“…36 Geographical locations and the costs of transport are also barriers to maternal and child healthcare in low and middle income countries. [38][39][40] The current study found that girls' preference for using traditional healers was also a factor that affected their willingness to access healthcare services. The preference for using traditional healers is often cited in the literature [41][42] as approximately 80% of people in Africa use traditional medication, especially for maternal and reproductive health issues.…”
Section: Discussion 25mentioning
confidence: 68%